Characterization of Interleukin-33 and the IL-33 receptor complex - Ali, Shafaqat; Justus Liebig University Giessen (My University, 2009)
Two pivotal aspects of the IL-33 system are characterized in this study: First the composition and function of the IL-33 receptor complex on IL-33 responder cells and second the generation of biologically active IL-33 by the IL-33 producer cell. IL-33 binds to the IL-33 receptor alpha-chain (ST2) and as is shown here, this results in the recruitment of interleukin-1 receptor accessory protein (IL-1RAcP) as the co-receptor. The IL-33-dependent interaction of membrane bound and soluble form of IL-1RAcP and IL-33Ralpha-chain was demonstrated in co-immunoprecipitation assays. Lack of the IL-1RAcP abrogated responses to IL-33 and IL-1 in the mouse thymoma clone EL-4 D6/76. Responsiveness to IL-33 and IL-1 was restored with the expression of full length IL-1RAcP, while a mutant protein lacking the Toll/IL-1 Receptor domain (TIR) was not sufficient to restore IL-33 or IL-1 responsiveness in EL-4 D6/76 cells. Moreover the monoclonal antibody 4C5, which neutralizes IL-1beta effects by blocking of murine IL-1RAcP, inhibited IL-33-stimulated signaling in mouse thymoma cells and bone marrow-derived mast cells. In search for putative further components of the IL-33 receptor complex, TIR8 / SIGIRR was studied, as it was proposed to be a candidate IL-33 receptor component. Using wild type TIR8 and chimeric fusion proteins it could be excluded that TIR8/SIGIRR can substitue for IL-1RAcP as a co-receptor. Furthermore, no experimental proof could be generated to show that this molecule is participating in the signaling IL-33 receptor complex. Like IL-18 and IL-1beta, IL-33 was found to have strong immunomodulatory functions. However, whereas IL-1beta and IL-18 promotes pro-inflammatory and Th1-associated responses, IL-33 induces Th2-associated cytokines. In order to find the differential gene regulation in response to these cytokines, IL-1-, IL-18- and IL-33 -induced gene expression profiles were compared by microarray from a triple responsive T cell line. Although a large number of genes were regulated by the IL-1 family members, no differentially regulated gene could be identified, suggesting the use of the same signaling molecules/pathways by all three cytokines, at least in this cellular system. Common notion in the field is that IL-33, like IL-1beta and IL-18, requires processing by caspase-1 to a mature form, in order to achieve biological activity as a cytokine. Contrary to the current dogma, here it is described that IL-33 is biologically active as unprocessesed full length molecule. Full length IL-33 binds to the IL-33 receptor-alpha chain and mediates the recruitment of IL-1RAcP to activate cells. IL-33 is processed in cells, however not by caspase 1 to a mature, biologically active, IL-33 but instead it is cleaved by caspase 3 at aa175 to yield two products which are both unable to bind to the IL-33 receptor. Thus caspase 3 processing inactivates IL-33 as a cytokine. Full length IL-33 and its N-terminal caspase 3 breakdown product, however, translocate to the nucleus of the producing cell. Interestingly, bioactive IL-33 is not released by cells constitutively or after activation of the inflammasome as is the case with other IL-1 family members, like IL-1beta and IL-18. Thus, it is tempting to speculate that IL-33 is not a classical cytokine but a molecule with dual function which normally exerts its function in the nucleus of intact cells and only activates others cells via the IL-33 receptor complex if cells are destroyed. Thus IL-33 may act as an endogenous danger signal, to alert cells of the innate immune system of the destruction of the IL-33 producing cells during hypoxia or after mechanical injury to initiate a sterile inflammation.

Zwei zentral wichtige Aspekte des IL-33 Systems werden in dieser Studie charakterisiert: Zuerst der Aufbau und die Funktion des IL-33 Rezeptorkomplexes auf Zellen, die auf IL-33 reagieren und zweitens die Bildung des biologisch aktiven IL-33 durch die produzierende Zelle.IL-33 bindet an die IL-33 Rezeptor alpha-Kette (ST2) und, wie hier gezeigt, resultiert dies in der Rekrutierung des Interleukin-1 Rezeptor Akzessorischen Proteins (IL-1RAcP) als Korezeptor. Die IL-33- abhängige Wechselwirkung des Membran-gebundenen und löslichen IL-1RAcP und der IL-33Ralpha-Kette wurde in Ko-immunopräzipitationsexperimenten gezeigt. Das Fehlen des IL-1RAcP verhinderte Antworten auf IL-33 and IL-1 in der Maus Thymoma Linie EL-4 D6/76. Die Fähigkeit auf IL-33 und IL-1 zu reagieren, wurde durch die Expression des intakten IL-1RAcP wieder hergestellt, während eine Mutante, welcher die Toll/IL-1 Rezeptor Domäne (TIR) fehlte, nicht in der Lage war, die IL-33- oder IL-1-Antwort in EL-4 D6/76-Zellen wieder herzustellen. Darüberhinaus inhibierte der monoklonale Antikörper 4C5, welcher IL-1beta -Effekte durch das Blockieren des murinen IL-1RAcP zu neutralisieren vermag, die IL-33-stimulierte Signaltransduktion in Maus Thymoma Zellen und in Mastzellen, die frisch aus Knochenmark ausdifferenziert worden waren. Wie IL-18 und IL-1beta übt IL-33 starke immunmodulatorische Funktionen aus. Während IL-1beta und IL-18 jedoch proinflammatorische und Th1 -assoziierte Antworten fördern, induziert IL-33 Th2-assoziierte Zytokine. Um eine differentielle Genregulation in Antwort auf diese Zytokine herauszufinden, wurden IL-1-, IL-18- und IL-33 induzierte Genexpressionsprofile mittels Microarrays in einer Triple-responsiven T-Zelllinie aufgenommen und verglichen. Obwohl eine große Zahl von Genen durch die Mitglieder der IL-1 Familie reguliert wurden, konnten keine differenziell regulierten Gene identifiziert werden, was vermuten lässt, dass alle drei Zytokine denselben Signalweg nutzen, zumindest in dem untersuchten Zellsystem. Es wird in Fachkreisen allgemein angenommen, dass IL-33, wie IL-1beta und IL-18, das Prozessieren durch die Caspase-1 zur reifen Form benötigt, um als Zytokin biologisch aktiv sein zu können. Dem Dogma widersprechend, wird hier beschrieben, das IL-33 als unprozessiertes Molekül biologisch aktiv ist, also in seiner gesamten durch die Primärsequenz definierten Länge. Unprozessiertes IL-33 bindet an die IL-33 Rezeptor-alpha Kette und vermittelt die Rekrutierung von IL-1RAcP, um Zellen zu aktivieren. Dabei wird IL-33 in Zellen prozessiert, jedoch nicht durch Caspase 1 zu einer reifen, biologisch aktiven Form, sondern es wird durch Caspase 3 an Position175 gespalten, wobei zwei Produkte entstehen, die beide nicht in der Lage sind, an den IL-33 Rezeptor zu binden. Insofern inaktivert Caspase 3 IL-33 als Zytokin. Unprozessiertes IL-33 und sein N-terminales Caspase 3 -Abbauprodukt können jedoch in den Kern der produzierenden Zelle translozieren. Interessanterweise wird bioaktives IL-33 nicht durch die Zellen freigesetzt, weder konstitutiv noch nach Aktivierung des Inflammasoms, wie es der Fall ist mit anderen Mitgliedern der IL-1 Familie, z.B. IL-1beta und IL-18. Daher ist es verlockend zu spekulieren, dass IL-33 gar kein klassisches Zytokin ist, sondern ein Molekül mit dualer Funktion welches normalerweise seine Aufgaben im Kern der produzierenden Zelle ausübt und nur dann andere Zellen über den IL-33 Rezeptorkomplex aktiviert, wenn die produzierenden Zellen zerstört werden. Damit mag IL-33 als ein endogenes Alarmsignal wirken, welches Zellen des angeborenen Immunsystems darauf aufmerksam macht, dass Zellen durch Zerstörung zu Grunde gegangen sind, zum Beispiel nach Sauerstoffunterversorgung oder durch mechanische Verletzung, um eine sterile Entzündung in Gang zu setzen.
Charakterisierung von Innterleukin-33 und dem IL-33 Rezeptor Komplex
Keywords: Interleukin-1 family; Interleukin-33; signal transduction; cytokin signaling; ddc:570